Two cases of small bowel obstruction secondary to a swallowed potato. (21st December 2015) - Castren, E; Hakeem, A; Mahmood, N S; Aryal, K
Abstract : Bowel obstruction due to bezoars (compaction of ingested material within the gastrointestinal tract) is a rare, but well documented occurrence. In this paper, we present two cases of potato-induced small bowel obstruction. Both patients were approximately 50 years old and had cerebral palsy and learning disabilities, respectively. They presented with abdominal pain and bilious vomiting, with no medical or surgical history. Diagnosis of small bowel obstruction was confirmed by CT prior to taking the patients to the operating theatre, where whole potatoes were found to be obstructing each patient's bowel lumen. Both patients underwent laparotomy with enterotomy and removal of the potato. They both made a good recovery. Through a literature review of bezoar-induced bowel obstruction, these cases highlight important diagnostic and management principles.